Authentic Leadership on Work Engagement with Psychological Capital as a Mediating Variable - Alwan, Zaki; Andriani, Chichi (Universitas Negeri Padang, 2023)
The purpose of this study was to test and analyze: (1) the effect of authentic leadership on work engagement (2) the effect of authentic leadership on psychological capital (3) the effect of psychological capital on work engagement (4) the effect of authentic leadership on work engagement through psychological capital. This research is causal research. The population of this study were all employees in the finance department of PT SP Manufacturing Padang City with a total of 46 people. The sampling technique was taken using total sampling with the number of samples equal to the population of 46 people. Data collection was carried out using a questionnaire using a Likert scale. Data analysis was carried out using SmartPLS 4 software. The findings obtained from data processing in this study reveal that: (1) authentic leadership has a positive and significant effect on work engagement in the finance department employees of PT SP Manufacturing Padang City (2) authentic leadership has a positive and significant effect on psychological capital in the finance department employees of PT SP Manufacturing Padang City (3) psychological capital has a positive and significant effect on work engagement in the finance department employees of PT SP Manufacturing Padang City (4) authentic leadership has a positive and significant effect on work engagement through psychological capital in the finance department employees of PT SP Manufacturing Padang City.